Water mites (Hydrachnidia) of the Drawa River (NW Poland) - Andrzej Zawal; Lech Pietrzak; Roksana Malicka; Edyta Stępień (Persian Journal of Acarology)
The water mite communities of the River Drawa were investigated in the year 1988. The samples were taken in April, July and September. A total of 1349 specimens belonging to 52 species of water mites were collected. We decided to distingush Lebertia cf. gibbosa despite of its synonymization with L. ineaqualis, because we collected both species and found sound distinguishing features. The status of the species should be rechecked. The most abundant species was Hygrobates setosus (13.4%) followed by Sperchon papillosus (10.5%), S. clupeifer (9.8%), Torrenticola amplexa (8.5%), Hygrobates longipalpis and Limnesia maculata (each 7.0%), Hygrobates calliger (5.8%), Lebertia ineaqualis (5.2%) and Arrenurus albator (4%). The largest synecological group was rheophiles and rheobionts (71.1% specimens) followed by lake species (16.5%), small water bodies species (11.9%), species from astatic waters and crenophilous species (0.2% specimens). The most stagnophilous species were connected with marginal pools with and muddy bottom covered by plants and sections of river after lake or spring. More specimens (894) and species (31) were caught in the lotic zone of the river than in the lentic zone (455 specimens, 28 species). Rheophilous species were divided into two groups: one connected with lotic zones but with rather slow-flowing water and sandy bottom, and another one connected with fast-flowing water with gravel and stones on the bottom, partially covered by mosses.